2022
DOI: 10.3389/fmed.2021.777961
|View full text |Cite
|
Sign up to set email alerts
|

Gut Metagenome as a Potential Diagnostic and Predictive Biomarker in Slow Transit Constipation

Abstract: Slow transit constipation (STC) is one of the most frequent gastrointestinal diagnoses. In this study, we conducted a quantitative metagenomics study in 118 Chinese individuals. These participants were divided into the discovery cohort of 50 patients with STC and 40 healthy controls as well as a validation cohort of 16 patients and 12 healthy controls. We found that the intestinal microbiome of patients with STC was significantly different from that of healthy individuals at the phylum, genus, and species leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…However, in our study, their decrease in FC patients suggests that a certain abundance of Escherichia–Shigella and Klebsiella may benefit the balance of the intestinal microenvironment. Alistipes and Parabacteroides have been reported to increase in patients with slow transit constipation (STC), while Klebsiella is enriched in normal controls [ 24 ]. Such changes are consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, their decrease in FC patients suggests that a certain abundance of Escherichia–Shigella and Klebsiella may benefit the balance of the intestinal microenvironment. Alistipes and Parabacteroides have been reported to increase in patients with slow transit constipation (STC), while Klebsiella is enriched in normal controls [ 24 ]. Such changes are consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…All of the above were flora involved in the allergic immune response of the organism, suggesting that the emergence and progress of PUD may be strongly involved in the ecological immunity of the gastrointestinal microenvironment. Sequencing studies of slow transit constipation patients and colorectal cancer patients both identified significant enrichment of Alistipes and suggested that it could be used as a potential pathogenic genus and diagnostic marker for gastrointestinal diseases ( 45 , 46 ). Coprococcus_2 was significantly enriched as a probiotic in HC patients, and a clinical study of irritable bowel syndrome ( 47 ) reached similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…g_Pseudoramibacter-Eubacterium, the primary producer of short-chain fatty acids, can provide energy for intestinal cells and act as an anti-inflammatory factor in the intestinal tract by metabolizing dietary fiber [ 51 ]. However, studies [ 52 ] have shown that Eubacter has a high abundance in patients with constipation, which requires further study in the future.…”
Section: Discussionmentioning
confidence: 99%